Development of axiomatic design-based High Strength Concrete framework / Rudy Tawie … [et al.] - Tawie, Rudy; Othman, Siti Zaidah; Openg, Iskanda (2014)
High Strength Concrete (HSC) is a highly complex type of concrete that is characterized by a superior level of performance and properties that cannot be achieved using normal ingredients of water, cement and aggregates and conventional design procedures. The concrete industry is generally very competitive and many concrete companies have invested enormously in the development of concrete mix design. In the laboratory, technical personnel would try numerous mix proportions to design concrete with the desired strength and properties.